A real time evaluation of employment forecasts in Switzerland - Michael Graff; Massimo Mannino; Michael Siegenthaler (ETH Zurich, KOF Swiss Economic Institute, 2012)
We evaluate nowcasts and one- to four-quarter-ahead forecasts of Swiss full time equivalent jobs from 1998-2011, comparing forecasts of the KOF Swiss Economic Institute and of the State Secretariat for Economic Affairs with the outcome of the reference series. Both forecasts are biased downward, and they do not capture the trend of the reference series well. In addition, we show that the KOF Employment Indicator as well as the Employment Indicator of the Federal Statistical Office are useful to predict the evolution full time equivalent jobs with a lead of about one quarter.
Keywords: C52; C53; E27; 330; Forecasting employment; forecast evaluation; Swiss labor market; Beschäftigung; Prognoseverfahren; Schweiz